PERENCANAAN TANGGUL BANJIR SUNGAI LUSI HILIR - Rizka Arbaningrum; Jennifer Gerina Putri; Pranoto Sapto Atmojo; Dwi Kurniani (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Flooding is one of the natural disasters that have a major impact on human survival. Flooding problems that occur in Grobogan partly due to the overflow of the river is one of the Lusi River. Lusi River has a length of 161,13 km flowing from Bulu Rembang to meet with Serang River in Penawangan Grobogan. Flood discharge plan used in analyzing cross-section using a return period of 25 years Q25 = 900 m3/sec. A cross-sectional analysis of existing and planned performed using HEC-RAS software. The output of the HEC-RAS** software indicate whether or not fulfilled at the cross-river flood discharge. Lusi River flooding problems addressed in various ways, namely the improvement of cross-section, planning dikes, raising the existing levees, concrete parapet planning and strengthening slopes or cliffs are prone to landslides. Overall technical planning with an estimated value of construction costs Rp. 82,995,060,000.00. (eighty-two billion nine hundred and ninety-five million six hundred thousand dollars) with the duration of work for 25 weeks.